Consolos instalados em etapa posterior à concretagem de pilar com auxílio de adesivo químico - Damasceno, João Henrique Lannes (Universidade Federal de São Carlos, 2016)
One of the most important principles in the connections design is the continuous search for simple solutions. Maximum economy in the precast construction is achieved with simple connection elements, with adequate performance and quick installation. One of the alternatives to be considered during the project to improve the simplicity in the column production is to avoid holes and cuts in the formwork. Projections and holes in the forms are laborious and reduce its lifecycle. Then, in order to make the column production process easier, this work aims study the alternative of using chemical adhesive for fastening the corbel reinforcement after casting the column. The work presents a literature review about the main concepts that are important to this solution: Connections design, chemical anchors, corbels and strut and tie models. The research also contains an experimental program with 3 tests full scale specimens with equal dimensions short corbels. Were tested 2 postinstalled corbels with the main tie reinforcement fastened with adhesive anchor and 1 cast in corbel with the main tie reinforcement anchored with hooked 90 º bars. The cast in corbel (specimen A) was designed according to the recommendations of the standards NBR6118:2014 e NBR9062:2006, 1 post-installed corbel (specimen B) was designed with the same anchorage length of the cast in corbel and the other post-installed corbel was designed according to the recommendations of the chemical adhesive producer. This way, was possible evaluate the influence of the anchorage length in the corbel behavior and the safety of the solution comparing with a cast in corbel. The anchorage length did not influence the corbel behavior during the test. The specimen A presented the ultimate load of 400 kN, specimen B 340 kN and specimen C 377 kN. All of the specimens presented failure by flexure-tension in a ductile manner and ultimate loads higher than foreseen by standards and calculation models. The post-installed specimens (B and C) had a similar behavior, presented higher crack width and were less stiffer than the specimen A. Specimens B and C also presented an inclined crack in the anchorage region of the column that alert to a different stress distribution in the anchorage region. Thus the solution of post-installed corbels with adhesive anchors presented a satisfactory performance, further research is needed in order to reduce the crack widths in the corbel region and avoid the cracks in the column.
Post-installed corbels with adhesive anchor
Keywords: Ancoragens químicas; Adesivos químicos; Ligações; Consolos; Adhesive anchors; Chemical adhesive; Connections; Corbels; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL